2020
DOI: 10.7241/ourd.20201.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical patterns and associated comorbidities of vitiligo in Kandahar, Afghanistan. A case-control study

Abstract: Background: Vitiligo is an idiopathic acquired depigmentary skin/mucous membrane disorder. Main objective of this study was to find out demographic data, clinical patterns, and comorbidities associated with vitiligo in Kandahar, Afghanistan. Material and Methods: This was a case-control study conducted in Kandahar University Teaching Hospital between July 2017-June 2018. Descriptive statistics, Chi-square test, and logistic regression were used for data analysis. Results: A total of 400 patients (200 cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Boza made the same finding in their study cited above (14.23; 16.75; 9.15; and 3.6) [12]. Rahimi also mentioned the same [19].…”
Section: Quality Of Lifesupporting
confidence: 80%
See 2 more Smart Citations
“…Boza made the same finding in their study cited above (14.23; 16.75; 9.15; and 3.6) [12]. Rahimi also mentioned the same [19].…”
Section: Quality Of Lifesupporting
confidence: 80%
“…However, females were more affected than males with higher scores. Other authors reported the same findings [6,10,16,19].…”
Section: Quality Of Lifesupporting
confidence: 64%
See 1 more Smart Citation
“…Kikuchi et al reported hyperuricemia in vitiligo patients who have undergone narrowband UVB therapy. The immunomodulatory effect of UV radiation affects T lymphocytes, which attack melanocytes, resulting in increased nucleic acid turnover, thus causing hyperuricemia [5,6]. Therefore, the sun exposure in our patient, who had had vitiligo since childhood, might have been responsible for the increased uric acid levels and gouty tophi.…”
mentioning
confidence: 80%
“…Vitiligo has been associated with a spectrum of autoimmune conditions such as alopecia areata, thyroid disease, pernicious anaemia, Addison's disease and rarely systemic lupus erythematosus [2]. Ying Jin et al identified several chromosomal regions that appear to contribute to this epidemiological association including chromosome 17p13 [3].…”
Section: Discussionmentioning
confidence: 99%